Characteristic Evaluation of Organic Light-Emitting Diodes Prepared with Stamp Printing Technique - Apisit Chittawanij; Kitsakorn Locharoenrat (My University, 2017)
We have reported on a stamp printing technique that uses PET release film as a printing stamp to deposit TPBi thin film served as the electron transport layer of the organic light-emitting diodes. TPBi thin film was printed with a good uniformity and resolution. Effect of deposition conditions on optical and electrical properties and surface roughness of TPBi thin film have been studied under spectroscopy and atomic force microscopy, respectively. It is found that characteristic of TPBi thin film is improved via controlled stamp temperature and time. Since TPBi thin film exhibits the surface morphology comparable to that of conventional spin-coating thin film, our findings suggest that PET release film-based stamp printing approach is possible to use as an alternative deposition of the organic thin film as compared with a traditional one.
Keywords: Deposition; Organic Light-Emitting Diodes Research